(untitled) (Berlin, 2008)
Statistical implicative analysis is a data analysis method with a significant impact on a variety of areas ranging from pedagogical research to data mining. This volume collects significant research contributions from disciplines that benefit from SIA
Keywords: Statistics,Mathematical analysis,Thống kê,Phân tích toán học